A novel mutation causing type 1 Gaucher disease found in a Japanese patient with gastric cancer: A case report. Issue 27 (July 2018) - Hosoba, Sakura; Kito, Katsuyuki; Teramoto, Yukako; Adachi, Kaori; Nakanishi, Ryota; Asai, Ai; Iwasa, Masaki; Nishimura, Rie; Moritani, Suzuko; Kawahara, Masahiro; Minamiguchi, Hitoshi; Nanba, Eiji; et al.
Abstract: Rationale: Gaucher disease (GD) is an autosomal recessive disorder that leads to multiorgan complications caused by β-glucocerebrosidase deficiency due to mutations in the β-glucocerebrosidase-encoding gene ( GBA ). GD morbidity in Japan is quite rare and clinical phenotype and gene mutation patterns of patients with GD in Japan and Western countries differ considerably. Of Japanese patients with GD, 57% develop types 2 or 3 GD with neurologic manifestations and younger onset, whereas only 6% of patients with GD develop those manifestations in Western countries. Thus, it is relatively difficult to find and diagnose GD in Japan. Patient concerns: A 69-year-old Japanese female with mild anemia and thrombocytopenia but without neurologic symptoms was initially referred for gastric cancer. Preoperative 18 F-deoxyglucose positron emission tomography/computed tomography (FDG PET/CT) showed accumulation in the bone marrow and paraabdominal lymph nodes. Following bone marrow aspiration found, abnormal foamy macrophages in the bone marrow and electron microscopy revealed that the macrophages were filled with tubular-form structures. Adding to these signs suggestive of a lysosomal disease, serum β-glucocerebrosidase activity test found decreased. Sequencing of the patient's GBA gene revealed a RecNciI recombinant mutation and the novel mutation K157R (c.587A>G). Diagnoses: On the basis of these findings and clinical manifestations, the final diagnosis of type 1 GD was made. Interventions: Enzyme replacement therapy (ERT) with velaglucerase α was started after the diagnosis of type 1 GD. Outcomes: The patient's β-glucocerebrosidase activity as well as hemoglobin and platelet levels were restored by ERT without any side effects. Bone marrow aspirations 10 months after the start of the treatment with velaglucerase α showed reduction of Gaucher cells in bone marrow to 2% from 4% of total cellularity. Lessons: This is the first report of 18 F-FDG PET/CT application providing a clue for GD diagnosis. A novel mutation in GBA is described, which implies a potential pool of patients with GD with this mutation in Japan.